BUILDING PROTECTION DESIGN IN FIRE HAZARD PREVENTION (CASE STUDY: FAJAR UNIVERSITY BUILDING (UNIFA) MAKASSAR) - Amrullah, Amrullah; Erniati, Erniati; Chaerul, Muhammad (Universitas Ibn Khaldun Bogor, 2022)
The growth and arrangement of existing buildings are sometimes not balanced with the readiness of building and urban infrastructure. The main danger of fire for humans is poisoning due to inhalation of smoke, about 75% of human deaths in burning buildings are caused by smoke, about 25% of deaths are caused by heat generated by fire. To carry out the functions and uses, the building consists of several systems, the system consists of sub-systems that form integrally in a single unit. Fire prevention is one of the building systems, which aims to save lives. Fire prevention is one aspect of building safety. To find out and assess the level of reliability of a building against fire hazards, a problem formulation is formulated, namely How to design a fire prevention analysis that can be applied to buildings. The conclusion that can be drawn regarding the design of a fire prevention inspection system and its application is, the design of a building reliability inspection system in fire prevention is one of the tools in assessing and inspecting buildings for fire prevention measures in buildings. Inspection of building reliability in fire prevention is carried out at the smallest level or on building components, can provide a more detailed assessment/inspection of the fire prevention system, Assessment of Rescue Means Components, Assessment of Active Protection Components, Passive Protection Assessment Means.